The puzzle of India's governance: culture, context and comparative theory - Mitra, Subrata Kumar (Routledge advances in South Asian studies, 2006)
Introduction : a comparative theory of governance -- Measuring governance : a design for empirical inquiry -- The institutional arrangement of governance : structure and the formation of the state in India -- The regional context of governance : six analytic narratives -- Policing and strategic reform : culture, context and welfare in the organisation of order -- The agency of public institutions : leaders, administrators, and governance -- Modern state and pre-modern identities : culture and governance in changing societies -- Negotiating governance in changing societies : beyond the Indian model
Includes bibliographical references
Keywords: India -- Politics and government -- 1977-; Geschichte 1947-; Governance; Indien; Geschichte 1977-; Politik